RELATION OF DISEASE ETIOLOGY AND RISK FACTORS TO HEART FAILURE WITH PRESERVED OR REDUCED EJECTION FRACTION: INSIGHTS FROM THE NATIONAL HEART, LUNG, AND BLOOD INSTITUTE’S FRAMINGHAM HEART STUDY - Lee, Douglas S. (2009)
BACKGROUND: The contributions of risk factors and disease etiology to heart failure with preserved ejection fraction (HFPEF) vs. heart failure with reduced ejection fraction (HFREF) have not been fully explored. METHODS AND RESULTS: We examined clinical characteristics and risk factors at time of heart failure (HF) onset, and long-term survival in Framingham Heart Study participants according to left ventricular ejection fraction ≤45% (n=314, 59%) vs. >45% (n=220, 41%) and hierarchical etiologic classification. HF was attributed to coronary heart disease (CHD) in 278 participants (52%), valvular heart disease in 42 (8%), hypertension in 140 (26%), or other/unknown etiologies in 74 (14%). Multivariable predictors of HFPEF (vs. HFREF) included elevated systolic blood pressure (odds ratio [OR]=1.13 per 10 mmHg, 95% CI; 1.04–1.22), atrial fibrillation (OR=4.23, 95% CI; 2.38–7.52), and female sex (OR=2.29, 95% CI; 1.35–3.90). Conversely, prior myocardial infarction (OR=0.32, 95% CI; 0.19–0.53) or left bundle-branch block QRS morphology (OR=0.21, 95% CI; 0.10–0.46) reduced the odds of HFPEF. Long-term prognosis was grim with a median survival of 2.1 years (5-year mortality rate: 74%), and was equally poor in men and women with HFREF or HFPEF. CONCLUSIONS: Among community patients with new-onset HF, there are differences in etiology and time-of-onset clinical characteristics between those with HFPEF versus HFREF. In people with HFREF, mortality is increased when CHD is the underlying etiology. These findings suggest that HF with reduced vs. preserved left ventricular systolic function are partially distinct entities, with potentially different approaches to early detection and prevention.